Optimalisasi Intervensi Terapi Musik Klasik Terhadap Penurunan Tingkat Halusinasi Pendengaran Pada Pasien Gangguan Jiwa Di Rsjd Dr.Rm.Soedjarwadi Klaten Provinsi Jawa Tengah - Nadia Sulisti Azizah; Sitti Rahma Soleman; Wahyu Reknoningsih (STIKes Ibnu Sina Ajibarang, 2024)
Background: Mental disorders are the condition of a person who has experienced disturbances in psychiatric functions, such as thought processes, emotions, willpower and psychomotor behavior. This type of music therapy is used for a variety of conditions including psychiatric disorders, medical problems, physical disability conditions, sensory disorders, developmental disabilities, and aging issues, to improve study concentration, support physical exercise, and stress and anxiety. Objective: To determine the results of the implementation of classical music therapy on the reduction of auditory hallucinations in patients with mental disorders at Dr. RM Hospital. Soedjarwadi Klaten. Methods: In this study, using the pre-test and post-test case study method conducted on two respondents, hallucination measurements were carried out with AHRS (Auditory Hallucinations Rating Scale), then classical music therapy was given for three days with a frequency of 1 time a day within 10-15 minutes. Results: The results obtained from the description and discussion above show that after 3 days of intervention on both respondents Mrs. M and Mrs. S respectively, namely 36:35, there was a significant decrease in auditory hallucination scores. Conclusions: There was a decrease in symptoms and hallucinations in both respondents after being given the classical music intervention with